Interpretations of meaning in mathematical education - Skovsmose, Ole [UNESP] (FapUNIFESP (SciELO), 2018)
As a starting point for an interpretation of meaning in mathematics education, let us consider two fictitious Brazilian children, Paul and Eloisa. They differ in life experiences, and such differences refer to social, economic, cultural, and religious conditions, and also point of views, assumptions and prejudices that could construct something meaningful or meaningless. In order to articulate the socio-political formation of meaning experiences, I present an interpretation of meaning with references in the students' foregrounds. The basic idea is to recognize that foregrounds are formed by a number of socio-political factors. These factors are discussed in terms of polarized, destroyed, amputated, directed, and multiplied foregrounds.
Interpretações de Significado em Educação Matemática
Keywords: Amputee foregrounds; Destroyed foregrounds; Directed foregrounds; Multiplied foregrounds; Polarized foregrounds